TRANSFORMASI KURIKULUM PESANTREN: Telaah Pemikiran KH. MA. Sahal Mahfudh dan Nurcholish Madjid - Effendi, Mukhlison; Suradi, Suradi (IAIN Ponorogo, 2014)
Abstract; Islamic boarding school is an indigenous Indonesia. Some contribution that given in the Islamization process, create a good community literacy and culture are very large. One reason, because there are Islamic boarding school curriculum transformation. Most influential enticement are KH. MA. Sahal Mahfudh and Nurcholish Madjid enticement. To knowing and determine the transformation both of those figures, the researcher take focus of study as: 1) the speculation of KH. MA. Sahal Mahfudh about islamic boarding school curriculum transformation. 2) The speculation of Nurcholish Madjid about islamic boarding school curriculum transformation. 3) The equation and differences between KH. MA. Sahal Mahfudh and Nurcholish Madjid speculation about Islamic boarding school curriculum transformation.Based on the focus of the study above, the researcher tries to answer through some research with use descriptive approach and library research types, while the data collection that used in this research is literary techniques. The data analysis that used in this research consisted of content analysis and comparative analysis.The conclusion of this study are both of KH. MA. Sahal Mahfudh and Nurcholish Madjid made an offer about Islamic boarding school curriculum transformation. The equation of their speculation about Islamic boarding school curriculum transformation occur in all of component of curriculum. The differences both of their speculation site in how to formulate Islamic boarding school curriculum transformation. KH. MA. Sahal Mahfudh take a more specific formulation in this transformation, whereas Nurcholish Madjid make a global transformation. Moreover, caused of the different interpretation of the motto al-muha>fazotu âala al-qodimi al-solih wa al-akhdu bi al-jadidi al-aslahu.Â Ù ÙØ®Øµ: Ø§ÙØ¨Ø³ÙØªØ±ÙÙØ§Øª ÙÙ Ø§ÙÙ Ø¤Ø³Ø³Ø© Ø§ÙØªØ¹ÙÙÙ ÙØ© Ø§ÙØ£ØµÙÙØ© ÙØ¯Ù Ø¥ÙØ¯ÙÙÙØ³ÙØ§. ÙÙÙØ§ Ø§Ø³ÙØ§Ù Ø§Øª ÙØ¨ÙØ±Ø© ÙÙ Ø¥Ø³ÙØ§Ù ÙØ© Ø§ÙÙ Ø¬ØªÙ Ø¹ Ø§ÙØ¥ÙØ¯ÙÙÙØ³Ù Ø§ÙÙ Ø«ÙÙ. ÙÙØ°Ø§ Ø¨ØªØºÙÙØ± Ø§ÙÙ ÙÙØ¬ ÙÙ Ø§ÙØ¨Ø³ÙØªØ±ÙÙØ§Øª. ÙÙÙ ÙØ°Ø§ Ø§ÙØµØ¯Ø¯ ØªØ¸ÙØ± Ø£ÙÙ ÙØ© ÙÙØ±Ø© ÙÙØ§ÙÙ Ø§ÙØØ§Ø¬ Ø³ÙÙ Ù ØÙÙØ¸ ÙÙÙØ± Ø®Ø§ÙØµ Ù Ø¬ÙØ¯. ÙÙÙ Ø¹Ø±ÙØ© ÙÙØ±ØªÙÙ Ø§ Ø£ÙØ«Ø±Ø¹Ù ÙØ°Ø§ ÙØ§ÙØ¨Ø§ØØ« ÙØ±ÙØ² Ø¨ØØ«Ù ÙÙ : 1) ÙÙØ±Ø© ÙÙØ§ÙÙ Ø§ÙØØ§Ø¬ Ø³ÙÙ Ù ØÙÙØ¸ Ø¹Ù ØªØºÙÙØ± Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙ Ø§ÙØ¨Ø³ÙØªØ±ÙÙØ§ØªØ 2) ÙÙØ±Ø© ÙÙØ± Ø®Ø§ÙØµ Ù Ø¬ÙØ¯ Ø¹Ù ØªØºÙÙØ± Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙ Ø§ÙØ¨Ø³ÙØªØ±ÙÙØ§ØªØ ÙØ§ÙÙØ±Ù Ø¨ÙÙÙÙ Ø§ ÙØ£ÙØ¬Ù Ø§ÙØªØ´Ø§Ø¨ÙÂ Ø¨ÙÙÙÙ Ø§ ÙÙ ÙØ°Ù Ø§ÙÙ Ø³Ø£ÙØ©. Ø§ÙØ·ÙØ§ÙØ§ Ù Ù Ù ÙØ¶ÙØ¹ Ø§ÙØ¨ØØ« Ø§ÙØ³Ø§Ø¨ÙØ ÙØØ§ÙÙ Ø§ÙØ¨Ø§ØØ« Ø¥Ø¬Ø§Ø¨Ø© Ø§ÙØ£Ø³Ø¦ÙØ© Ø¹Ù Ø·Ø±ÙÙ Ø§ÙØ¨ØØ« Ø¨Ø§ÙÙ Ø¯Ø®Ù Ø§ÙÙØµÙÙ ÙÙÙØ¹Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙ ÙØªØ¨ÙØ©. Ø§Ø³ØªØ®Ø¯Ù Ø§ÙØ¨Ø§ØØ« ÙØ¬Ù Ø¹ Ø¨ÙØ§ÙØ§Øª Ø§ÙØ¨ØØ« Ø£Ø³ÙÙØ¨ Ø§ÙÙØ«Ø§Ø¦Ù Ø§ÙÙ ÙØªÙØ¨Ø©Ø ÙÙØ§Ù Ø§ÙØªØÙÙÙ ØªØÙÙÙ Ø§ÙÙ Ø¶Ù ÙÙ ÙØ§ÙØªØÙÙÙ Ø§ÙÙ ÙØ§Ø±Ù. ÙÙØªÙØ¬Ø© Ø§ÙØ¨ØØ« Ø¥ÙÙÙ Ø§ ( Ø³ÙÙ Ù ØÙÙØ¸ ÙÙÙØ± Ø®Ø§ÙØµ Ù Ø¬ÙØ¯) Ø§ÙØªØ±ØØ§ Ø·Ø±Ø§Ø² ØªØºÙÙØ± Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙ Ø§ÙØ¨Ø³ÙØªØ±ÙÙØ§Øª. ÙØ£Ù Ø§ Ø£ÙØ¬Ù Ø§ÙØªØ´Ø§Ø¨Ù Ø¨ÙÙ ÙÙØ±ØªÙÙ Ø§ ØªÙÙÙ ÙÙ Ø¬Ù ÙØ¹ Ø¹ÙØ§ØµØ± Ø§ÙÙ ÙÙØ¬. ÙØ§ÙÙØ±Ù Ø¨ÙÙ ÙÙØ±ØªÙÙ Ø§ ÙÙÙÙ ÙÙ ÙÙÙÙØ© ØªÙÙÙÙ ÙØ°Ø§ Ø§ÙØªØºÙÙØ± ÙÙ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù. Ø§ØªØ®Ø° Ø³ÙÙ Ù ØÙÙØ¸ Ø§ÙØªÙÙÙÙ Ø§ÙØ®Ø§Øµ ÙÙ ÙØ°Ø§ Ø§ÙØ£Ù Ø± ÙØ£Ù Ø§ ÙÙØ± Ø®Ø§ÙØµ Ù Ø¬ÙØ¯ ÙØ§ØªØ®Ø° Ø·Ø±Ø§Ø² Ø§ÙØªÙÙÙÙ Ø§ÙØ¹Ø§Ù . ÙÙØ°Ø§ ÙØªÙØ¬Ø© ÙØ¬ÙØ¯ Ø§ÙØ§Ø®ØªÙØ§Ù ÙÙ ÙÙÙ ÙØªÙØ³ÙØ± Ø§ÙÙØ§Ø¹Ø¯Ø©